The Fate of Inhaled Nanoparticles: Detection and Measurement by Enhanced Dark-field Microscopy. (January 2018) - Mercer, Robert R.; Scabilloni, James F.; Wang, Liying; Battelli, Lori A.; Antonini, James M.; Roberts, Jenny R.; Qian, Yong; Sisler, Jennifer D.; Castranova, Vincent; Porter, Dale W.; Hubbs, Ann F.
Assessing the potential health risks for newly developed nanoparticles poses a significant challenge. Nanometer-sized particles are not generally detectable with the light microscope. Electron microscopy typically requires high-level doses, above the physiologic range, for particle examination in tissues. Enhanced dark-field microscopy (EDM) is an adaption of the light microscope that images scattered light. Nanoparticles scatter light with high efficiency while normal tissues do not. EDM has the potential to identify the critical target sites for nanoparticle deposition and injury in the lungs and other organs. This study describes the methods for EDM imaging of nanoparticles and applications. Examples of EDM application include measurement of deposition and clearance patterns. Imaging of a wide variety of nanoparticles demonstrated frequent situations where nanoparticles detected by EDM were not visible by light microscopy. EDM examination of colloidal gold nanospheres (10–100 nm diameter) demonstrated a detection size limit of approximately 15 nm in tissue sections. EDM determined nanoparticle volume density was directly proportional to total lung burden of exposed animals. The results confirm that EDM can determine nanoparticle distribution, clearance, transport to lymph nodes, and accumulation in extrapulmonary organs. Thus, EDM substantially improves the qualitative and quantitative microscopic evaluation of inhaled nanoparticles.